Manual of Midwifery : and gynaecological nursing - Jacob, Annamma (New Delhi, India : Jaypee Brothers Medical Publishers, 2012)
The manual is intended for use as study and reference material for nursing students and professional nurses, practising midwifery and gynaecological nursing.
Contents De la A a la Z
incluye appendix ; bibliography ; index
Keywords: ENFERMERIA; GINECOLOGÍA